Juvenile detention and educational engagement: A sociocultural analysis inspired by Vygotskij - Miklósi, Márta (Form@re - Open Journal per la formazione in rete, 2025)
The detention of juvenile offenders poses significant risks to healthy psychosocial development and to a successful transition into adulthood, exposing an already vulnerable population to a range of adverse outcomes. This study addresses the issue through the lens of Vygotskij’s sociocultural theory, which offers a conceptual framework for understanding how relationships with significant others and institutional environments shape young people’s identity formation and personality development. Specifically, we examine the role of education within juvenile custodial settings. The findings suggest that active engagement in education has multifaceted benefits: beyond its well-documented positive effects on learning, it also reconnects young people to a normative developmental trajectory that may foster processes of desistance. Detenzione minorile e impegno educativo: un’analisi socioculturale di ispirazione vygotskiana. La detenzione dei minori autori di reato comporta rischi significativi per un sano sviluppo psicosociale e per una transizione efficace all’età adulta, esponendo una popolazione già vulnerabile a una serie di esiti sfavorevoli. Il presente studio affronta la questione attraverso la prospettiva della teoria socioculturale di Vygotskij, che offre un quadro teorico per comprendere come le relazioni sociali e i contesti istituzionali incidano sulla formazione dell’identità e sullo sviluppo della personalità dei giovani. In particolare, il saggio prende in esame il ruolo dell’educazione nei contesti di detenzione minorile. I risultati indicano che un coinvolgimento attivo nei percorsi educativi produce benefici molteplici: oltre ai noti effetti positivi sull’apprendimento, esso contribuisce a ricondurre i giovani verso una traiettoria di sviluppo normativo che può favorire i processi di desistenza.